Dependence of Neuroprosthetic Stimulation on the Sensory Modality of the Trigeminal Neurons Following Nerve Injury. Implications in the Design of Future Sensory Neuroprostheses for Correct Perception and Modulation of Neuropathic Pain - Virtuoso, Assunta; Herrera-Rincon, Celia; Papa, Michele; Panetsos, Fivos (Frontiers in Neuroscience, 2019)
Amputation of a sensory peripheral nerve induces severe anatomical and functional changes along the afferent pathway as well as perception alterations and neuropathic pain. In previous studies we showed that electrical stimulation applied to a transected infraorbital nerve protects the somatosensory cortex from the above-mentioned sensory deprivation-related changes. In the present study we focus on the initial tract of the somatosensory pathway and we investigate the way weak electrical stimulation modulates the neuroprotective-neuroregenerative and functional processes of trigeminal ganglia primary sensory neurons by studying the expression of neurotrophins (NTFs) and Glia-Derived Neurotrophic Factors (GDNFs) receptors. Neurostimulation was applied to the proximal stump of a transected left infraorbitary nerve using a neuroprosthetic micro-device 12 hours/day for four weeks in freely behaving rats. Neurons were studied by in situ hybridization and immunohistochemistry against RET (proto-oncogene tyrosine kinase “rearranged during transfection”), tropomyosin-related kinases (TrkA, TrkB, TrkC) receptors and IB4 (Isolectin B4 from Griffonia simplicifolia). Intra-group (left vs. right ganglia) and inter-group comparisons (between Control, Axotomization and Stimulation-after-axotomization groups) were performed using the mean percentage change of the number of positive cells per section [100*(left-right)/right)]. Intra-group differences were studied by paired t-tests. For inter-group comparisons ANOVA test followed by post hoc LSD test (when P<0.05) were used. Significance level (α) was set to 0.05 in all cases. Results showed that (i) neurostimulation has heterogeneous effects on primary nociceptive and mechanoceptive/proprioceptive neurons; (ii) neurostimulation affects RET-expressing small and large neurons which include thermo-nociceptors and mechanoceptors, as well as on the IB4- and TrkB-positive populations, which mainly correspond to non-peptidergic thermo-nociceptive cells and mechanoceptors respectively. Our results suggest (i) electrical stimulation differentially affects modality-specific primary sensory neurons (ii) artificial input mainly acts on specific nociceptive and mechanoceptive neurons (iii) neuroprosthetic stimulation could be used to modulate peripheral nerve injuries-induced neuropathic pain. These could have important functional implications in both, the design of effective clinical neurostimulation-based protocols and the development of neuroprosthetic devices, controlling primary sensory neurons through selective neurostimulation.